Evaluación del riesgo a la salud humana asociado al consumo de peces contaminados por metales pesados en el embalse del Guájaro, Atlántico-Colombia (2020)
The concentrations of heavy metals (Hg, Pb, Zn and Cr) in the muscle tissue of some fish species of the Guájaro reservoir located in the department of Atlántico, Colombia were evaluated. The evaluated species were: mojarra negra (Oreochromis niloticus), arenca (Tryportheus magdalenae), barbudo (Pimelodus blochii), doncella (Ageneiosus cáucanus), viejito (Cypocharax magdalenae), mojarra amarilla (Caquetaia kraussi), pacora (Plagioscion magdalenae) and tilapia (Oreochromis spp).The samples were analyzed by atomic absorption spectrometry. The highest concentrations were presented in the following order: Zn> Cr> Pb> Hg, in the species Tryportheus magdalenae (14.2 ± 1.482 μg / g), Tryportheus magdalenae (0.862 ± 0.790 μg / g), Caquetaia krausii (0.088 ± 0.063 μg / g) and Plagioscion magdalenae (0.222 ± 0.08 μg / g), respectively. To the contrary, the lowest concentrations presented the following order: Pb <Hg <Cr <Zn, in the species Plagioscion magdalenae (0.012 ± 0.005 μg / g), Ageneiosus pardalis (0.12 ± 0.05 μg / g), Oreochromis spp. (0.413 ± 0.14 μg / g) and Pinelodus blochii (5 ± 1.21 μg / g), respectively. Likewise, none of the concentrations exceeded the permissible limits established by FAO, WHO, EC and NTC 1443. The estimation of the potential risk (PR) associated with fish consumption identified that none of the species studied in the present investigation exceeded the PR value <1, however, chromium was the metal that showed the highest potential risk for the population, with a value of 0.87. Based on the results obtained, it is recommended to establish measures to control the consumption of the species and reduce exposure to metals, taking into account that their bioaccumulation over time would cause public health problems to the community of the Guajaro reservoir.